THE ROLE OF MANAGERIAL LEADERSHIP IN MAINTAINING OF THE EXISTENCE OF PRIVATE ISLAMIC UNIVERSITIES IN DISRUPTION ERA - Marlina, Yuli; Siregar, Mulki; Iryani, Endang; Oktoriano, Adriano (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This study aims to analyse the role of managerial leadership in facing disruption in Private Islamic Universities (PTIS) in Jakarta. The main focus is on how adaptive and visionary leadership can help PTIS manage change, make strategic decisions, and motivate the team to achieve the institution's goals. The method used is qualitative with a literature study approach. Data is collected from various secondary sources such as books, scientific journals, articles, and reports relevant to the research topic. Data analysis was carried out using thematic analysis techniques to identify key themes related to managerial leadership strategies. The results of the study show that adaptive and visionary managerial leadership is very important in facing the era of disruption. PTIS leaders need to develop innovative strategies in the curriculum, use of technology, and effective human resource management. In addition, building an organizational culture that supports change and innovation is also crucial. This study also identified that several private universities in Jakarta have been closed due to various factors such as low academic quality, management problems, and lack of student interest. Therefore, effective managerial strategies, including the adoption of educational technology, curriculum adjustments, staff development, global collaboration, and good financial management, are indispensable to maintain the existence of PTIS in this disruption era. This research provides valuable insights for PTIS leaders in facing the challenges of disruption and ensuring the sustainability of their institutions.